Exploring Political Budget Cycles in the EU-27 - António Afonso; José Alves; Frederico Silva Leal (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
Using quarterly data for the period Q1:2000–Q4:2024, the study examines whether elections in EU‑27 member states shape the composition and timing of fiscal policy strategies, and how political, fiscal and institutional constraints condition these dynamics. Employing a two‑way fixed‑effects framework, we find evidence that elections consistently lead to increases in primary expenditure. These effects are visible across several components, namely compensation of employees, intermediate consumption, gross fixed capital formation, and other primary expenditure. Using alternative electoral windows reveals that some adjustments begin before the electoral year, particularly in the case of GFCF and other primary expenditure, suggesting medium‑term planning of politically salient spending. Importantly, these patterns emerge only around regular elections, with no evidence of political budget cycles in early elections. In addition, high‑debt countries tend to adopt more restrictive electoral strategies, EU membership moderates pre‑electoral spending, and coalition governments appear to impose additional fiscal discipline during election periods. Overall, the findings indicate that political budget cycles persist in the European Union, but their magnitude and composition depend critically on fiscal conditions, institutional frameworks, and governance structures.
Keywords: D72; E62; H60; 330; political budget cycles; fiscal policy; elections; European Union